2019
DOI: 10.1111/ijlh.13093
|View full text |Cite
|
Sign up to set email alerts
|

The hypercoagulable state in multiple myeloma: The contribution of thrombin generation test

Abstract: Background Multiple myeloma is a hematologic malignancy which confers a high venous thromboembolic risk. This risk is linked to patient‐related factors, disease‐specific mechanisms, and antimyeloma therapy, especially immunomodulatory drugs. Some studies have suggested that the thrombin generation assay may be a predictive marker of thrombosis. This study aimed to assess the hypercoagulable state in patients with multiple myeloma at diagnosis and after myeloma therapy. Methods Thirty‐one patients with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…A recent study assessed thrombin generation, procoagulant phospholipids (PPL), neutrophil extracellular traps (NETs) and circulating microvesicle (MV)-associated TF in 38 patients and 19 MGUS patients, and compared them to healthy controls [ 14 ]. As confirmed by other studies [ 38 , 39 , 40 ], MM and MGUS patients have increased thrombin generation and PPL activity compared to healthy controls. Cell-free DNA (cfDNA) is not a specific marker of NETs and increased thrombotic risk in MM patients, but it may reflect NETs formation [ 41 , 42 , 43 ].…”
Section: Literature Reviewsupporting
confidence: 79%
“…A recent study assessed thrombin generation, procoagulant phospholipids (PPL), neutrophil extracellular traps (NETs) and circulating microvesicle (MV)-associated TF in 38 patients and 19 MGUS patients, and compared them to healthy controls [ 14 ]. As confirmed by other studies [ 38 , 39 , 40 ], MM and MGUS patients have increased thrombin generation and PPL activity compared to healthy controls. Cell-free DNA (cfDNA) is not a specific marker of NETs and increased thrombotic risk in MM patients, but it may reflect NETs formation [ 41 , 42 , 43 ].…”
Section: Literature Reviewsupporting
confidence: 79%
“…Several studies have tried to study coagulation in MM-patients with standard plasma thrombin generation profiles. The results of those studies were inconclusive: some studies observed an increased TG (ETP) in PPP ( 29 32 ), other studies, including ours, found no difference between MM patients and controls ( 33 , 34 ) while there are also studies that reported a reduced TG (ETP) in MM patients ( 35 , 36 ). One study observed no effect on the ETP and Peak, however, the TTP was reduced and the velocity index increased in MM patients compared to controls ( 37 ).…”
Section: Discussionmentioning
confidence: 72%
“…In addition, tumor cells metastasize and invade tissues and organs, resulting in tissue damage and endothelial cell damage. After endothelial cell injury, a large number of tissue factors can be released to activate the body's coagulation system, which then leads to coagulation-fibrinolysis dysfunction in patients [ 9 , 10 ]. D-dimer (D-D), fibrinogen (FIB), prothrombin time (PT), etc.…”
Section: Introductionmentioning
confidence: 99%